A Simple and Convenient Method for the Synthesis of 1-Methyl-7-arylfuro[3,2-g]pteridine-2,4(1H,3H)-diones and Their Substituted Derivatives - Maxim Stanislavovich Kazunin; Oleksii Yurievich Voskoboynik; Svetlana Valentynivna Shishkina; Oleksii Mykolayovych Antypenko; Sergey Ivanovich Kovalenko (Acta Chimica Slovenica, 2020)
A simple and effective method for the synthesis of unknown 1-methyl-7-arylfuro[3,2-g]pteridine-2,4(1H,3H)-diones by dehydration of the corresponding 1-methyl-6-phenacyl-pteridine-2,4,7(1H,3H,8H)-triones is reported in the article. It was shown that their alkylation by butyl chloroacetate in basic medium proceeded by the N3-atom of the heterocycle. The structure and purity of the synthesized compounds were confirmed by IR, 1H, 13C NMR spectroscopy, gas chromatography-mass spectrometry, mass spectrometry, as well as X-ray diffraction analysis. The proposed mechanism of the dehydration reaction was discussed.